Validation of the Thai Version of the Patient Health Questionnaire for Adolescents (PHQ-A) in adolescent psychiatric patients: Validation of the Thai version of the PHQ-A - Panyawong, Wimonwan; Pavasuthipaisit, Chosita; Santitadakul, Rattanasak (International Journal of Child Development and Mental Health, 2020)
A basic screening tool for depression for adolescents was insufficient in Thailand. Thus, Patient Health Questionnaire for Adolescents (PHQ-A) was translated into Thai. This study aimed to examine the psychometric properties of the Thai version of the PHQ-A. Samples were 11-20 year old patients who attended 12 child and adolescent psychiatric clinics across Thailand. Of 272 adolescent patients, 172 patients had depression and 100 patients did not have depression. To evaluate criterion validity, the PHQ-A scores were compared with the clinical diagnosis. Internal consistency and exploratory factor analysis (EFA) were also conducted for item and factor analysis Convergent validity was calculated from correlations between the PHQ-A and the Children’s Depression Inventory (CDI) and the Centre for Epidemiologic Studies-Depression Scale (CES-D). The internal consistency coefficient of the Thai version of the PHQ-A was 0.92. EFA suggested that one-factor structure of depressive symptoms was suitable for the PHQ-A. The area under the curve of the PHQ-A total score against professional diagnosis was 0.88. The results indicated an optimal cut-off point with acceptable sensitivity and specificity of 8. Moreover, the PHQ-A score of 10 was useful for differentiating between patients without depression and those with moderate to severe major depressive disorder (MDD). Convergent validity was good with high correlations for both the CDI and the CES-D (r=0.83 and 0.87, respectively). The Thai version of the PHQ-A is a valid and reliable measurement. The tool is simple and easy to use for screening and monitoring the severity of depressive symptoms in children and adolescents in both clinical and community settings.